Lack of β, β‐carotene‐9′, 10′‐oxygenase 2 leads to hepatic mitochondrial dysfunction and cellular oxidative stress in mice. Issue 5 (9th February 2017) - Wu, Lei; Guo, Xin; Hartson, Steven D.; Davis, Mary Abby; He, Hui; Medeiros, Denis M.; Wang, Weiqun; Clarke, Stephen L.; Lucas, Edralin A.; Smith, Brenda J.; von Lintig, Johannes; Lin, Dingbo
Abstract : β, β‐Carotene‐9′, 10′‐oxygenase 2 (BCO2) is a carotenoid cleavage enzyme localized to the mitochondrial inner membrane in mammals. The results of the current study demonstrate that the loss of BCO2 causes changes of the hepatic mitochondrial proteome, mitochondrial hyperactivation, and stress, leading to mitochondrial energy insufficiency. BCO2 appears to be critical for proper hepatic mitochondrial function in mice. Abstract : Scope: β, β‐Carotene‐9′, 10′‐dioxygenase 2 (BCO2) is a carotenoid cleavage enzyme localized to the inner mitochondrial membrane in mammals. This study was aimed to assess the impact of genetic ablation of BCO2 on hepatic oxidative stress through mitochondrial function in mice. Methods and results: Liver samples from 6‐wk‐old male BCO2 −/− knockout (KO) and isogenic wild‐type (WT) mice were subjected to proteomics and functional activity assays. Compared to the WT, KO mice consumed more food (by 18%) yet displayed significantly lower body weight (by 12%). Mitochondrial proteomic results demonstrated that loss of BCO2 was associated with quantitative changes of the mitochondrial proteome mainly shown by suppressed expression of enzymes and/or proteins involved in fatty acid β‐oxidation, the tricarboxylic acid cycle, and the electron transport chain. The mitochondrial basal respiratory rate, proton leak, and electron transport chain complex II capacity were significantly elevated in the livers of KO compared to WT mice. Moreover, elevated reactive oxygen species and increased mitochondrial protein carbonylation were also demonstrated in liver of KO mice. Conclusions: Loss of BCO2 induces mitochondrial hyperactivation, mitochondrial stress, and changes of the mitochondrial proteome, leading to mitochondrial energy insufficiency. BCO2 appears to be critical for proper hepatic mitochondrial function.